Myanmar : Capitalizing on Rice Export Opportunities - World Bank (Bangkok, 2014)
Improving agricultural productivity and promoting exports are top priorities for the Government of the Republic of the Union of Myanmar. Given the centrality of rice to the rejuvenation of agriculture in Myanmar, the rice sector is of critical importance, especially rice exports. The government announced ambitious targets of 2 million metric tons (tons)2 of rice exports by 2014/15 and 4 million tons by 2019/20. Recent actual performance is falling short of these targets, but the opening of Myanmar's economy has already helped significantly increase rice exports. The rest of the report is organized as follows. Chapter two provides information on recent rice export developments in Myanmar. Chapter three presents the evolving export opportunities as well as challenges that must be overcome to capitalize on them. Chapter four describes the main constraints at various segments of the value chain and offers possible remedies. Chapter five discusses how rice policy should evolve to support modernization of the rice value chain. Chapter six offers conclusions and policy recommendations. Seven annexes provide further, more detailed information.